Guillaume des Moustiers treatise on the armillary instrument (1264) and the practice of astronomical observation in medieval Europe - Nothaft, Carl (My University, 2021)
This article is devoted to a thirteenth-century Latin text on how to construct, set up, and use a version of the so-called armillary instrument (instrumentum armillarum), which was first described in Ptolemy’s Almagest as a tool for measuring ecliptic coordinates. Written in 1264 by Guillaume des Moustiers, bishop of Laon, this hitherto unstudied Tractatus super armillas survives in a single manuscript, where it is accompanied by a copious set of glosses. The text and its glosses jointly offer an unusually detailed account of the instrument’s material aspects and methods of assembly. In addition, they reflect a keen awareness of the potential sources of error that may arise in the context of astronomical observation, while making suggestions on how these errors may be minimized or avoided. The Tractatus super armillas accordingly is a valuable source on the observational side of medieval European astronomy, which has often been minimized in modern historical accounts.
PUBLISHED
Keywords: Medieval astronomy; Thirteenth-century; Astronomical observation; Astronomical instruments; Armillary instrument; Ptolemy; Manuscript, Book and Print Cultures